2019
DOI: 10.1634/theoncologist.2019-0129
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Nivolumab plus Low-Dose Ipilimumab in Previously Treated Microsatellite Instability-High/Mismatch Repair-Deficient Metastatic Colorectal Cancer

Abstract: Background Early detection and management of treatment‐related adverse events (TRAEs) in patients receiving immune checkpoint inhibitors may improve outcomes. In CheckMate 142, nivolumab (3 mg/kg) plus low‐dose ipilimumab (1 mg/kg) provided durable clinical benefit (objective response rate [ORR] 55%, median duration of response not reached, 12‐month overall survival [OS] rate 85%) and manageable safety for previously treated microsatellite instability‐high and/or mismatch repair‐deficient (MSI‐H/dMMR) metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…The CheckMate142 study confirmed that mCRC with MSI-H/dMMR treated with nivolumab and pembrolizumab had an increased immune response compared with nivolumab monotherapy (79). Moreover, nivolumab has been approved for mCRC with MSI-H/dMMR following unsuccessful standard chemotherapy (80). Thus, MSI-H/dMMR has emerged as another immunotherapy-related biomarker for screening the subpopulation of patients that are likely to benefit from immunotherapy.…”
Section: Microsatellite Instability (Msi)-h/mismatched Repairdeficienmentioning
confidence: 91%
“…The CheckMate142 study confirmed that mCRC with MSI-H/dMMR treated with nivolumab and pembrolizumab had an increased immune response compared with nivolumab monotherapy (79). Moreover, nivolumab has been approved for mCRC with MSI-H/dMMR following unsuccessful standard chemotherapy (80). Thus, MSI-H/dMMR has emerged as another immunotherapy-related biomarker for screening the subpopulation of patients that are likely to benefit from immunotherapy.…”
Section: Microsatellite Instability (Msi)-h/mismatched Repairdeficienmentioning
confidence: 91%
“…382 Further studies argued that a combination of nivolumab and the CTLA-4 inhibitor ipilimumab surpassed single-agent immune checkpoint blocking with an acceptable rate of adverse events. [398][399][400] Combined therapy with nivolumab and ipilimumab helped patients with dMMR or MSI-H CRC who had previously received chemotherapy to reach a PFS of 71% and an OS of 85% at 1 year; 80% of them maintained disease control over 12 weeks. For firstline use of this doublet regimen, a new study assessed its efficacy and safety for patients with dMMR or MSI-H CRC.…”
Section: Immune Checkpoint Inhibitor Therapymentioning
confidence: 99%
“…In the nivolumab-only cohort, 31% of patients had an objective response and 12-month OS was 73% [ 74 ]. Among 119 patients, 25% had an endocrine, 23% had a gastrointestinal, 19% had hepatic, 5% had pulmonary, 5% had renal and 29% experienced skin irAEs; the majority (57%) were grade 1/2 [ 75 ]. The result of this study indicated nivolumab plus ipilimumab as a new treatment option for patients with MSI-high CRC.…”
Section: Combination Therapy In Different Cancersmentioning
confidence: 99%